Sodium-glucose co-transporter 2 (SGLT2) inhibitors: a growing class of anti-diabetic agents - Eva M Vivian (BioExcel Publishing Ltd, 2014)
Although several treatment options are available to reduce hyperglycemia, only about half of individuals with diagnosed diabetes mellitus (DM) achieve recommended glycemic targets. New agents that reduce blood glucose concentrations by novel mechanisms and have acceptable safety profiles are needed to improve glycemic control and reduce the complications associated with type 2 diabetes mellitus (T2DM). The renal sodium-glucose co-transporter 2 (SGLT2) is responsible for reabsorption of most of the glucose filtered by the kidney. Inhibitors of SGLT2 lower blood glucose independent of the secretion and action of insulin by inhibiting renal reabsorption of glucose, thereby promoting the increased urinary excretion of excess glucose. Canagliflozin, dapagliflozin, and empagliflozin are SGLT2 inhibitors approved as treatments for T2DM in the United States, Europe, and other countries. Canagliflozin, dapagliflozin, and empagliflozin increase renal excretion of glucose and improve glycemic parameters in patients with T2DM when used as monotherapy or in combination with other antihyperglycemic agents. Treatment with SGLT2 inhibitors is associated with weight reduction, lowered blood pressure, and a low intrinsic propensity to cause hypoglycemia. Overall, canagliflozin, dapagliflozin, and empagliflozin are well tolerated. Cases of genital infections and, in some studies, urinary tract infections have been more frequent in canagliflozin-, dapagliflozin-, and empagliflozin-treated patients compared with those receiving placebo. Evidence from clinical trials suggests that SGLT2 inhibitors are a promising new treatment option for T2DM.